수력발전기 On-line 부분방전 측정 시스템을 이용한 절연상태 진단의 신뢰성 향상 - 옥연호(Yeon-Ho Ok); 이은웅(Eun-Woong Lee); 임재일(Jae-Il Lim); 박지군(Ji-Kun Park); 곽원구(Won-Ku Kwak); 이재흥(Jae-Heung Lee); 신재필(Jae-Pil Shin); 신병철(Byoung-Chol Shin) (전기학회 논문지 P권, 58(4), 2009)
Accident dangerousness of domestic hydro power generators which are operated in Korea is on the increase because of use at the long term. On this, the Off-line diagnosis techniques developed to the On-line by continued domestic technical development since 2000. Especially, On-line insulation diagnosis of domestic hydro power generator is possible by localization of partial electric discharge sensor and On-line insulation diagnosis system. This paper shows the diagnosis result that is applied localized Ceramic Coupler and PDMS-HG(Partial Discharge Monitoring System for Hydro Generator) at four Chung-ju hydro Generator used for 25 years. Particularly, the confidence of insulation diagnosis is improved by using high frequency filter and sampling the partial discharge signals which occur in site. For reviewing the confidence of On-Line insulation diagnosis system, we measured the outside noises and partial discharge signals during practical operation by using the partial discharge diagnosis system of the Full A/D process. And we reviewed the confidence of the On-Line insulation diagnosis system by comparing and analyzing these data.